Pengaruh Pemberian Pupuk Organik pada Media Tanah yang Mengandung Timbal (Pb) terhadap Pertumbuhan Apu-apu (Pistia stratiotes) - Suriani, Siti; Handayani, Ida; Handayani, Susila (Biocaster : Jurnal Kajian Biologi, 2021)
Apu-apu (Pistia stratiotes) is a hyperaccumulator plant for lead (Pb), whereas apu-apu is widely consumed by the public. This study aimed to determine the growth and lead content (Pb) of Apu-Apu at various doses of organic fertilizer; and to determine the most effective dose of organic fertilizer to increase growth and reduce lead (Pb) content in Apu-apu. The study was conducted in a completely randomized design (CRD) with treatment with organic fertilizer at a dose of 0 grams, 50 grams, 100 grams, 150 grams, 200 grams, and 250 grams in 2 kg of soil from Ambon TPA. Each treatment was repeated 4 times and carried out for 4 weeks. Observations included plant height, number of leaves, leaf length, root length, and plant wet weight. At week 4, measurements of lead (Pb) levels in the leaves were carried out. ANOVA and 5% BNT were tested. The results showed that the application of organic fertilizer can increase the growth of Apu-apu plants. The most effective dose for Apu-apu plant growth is 200 grams in 2 kg of soil. The application of organic fertilizer could not reduce the Pb content in the Apu-apu plant.